Active vibration control of ship mounted flexible rotor-shaft-bearing system during seakeeping - Soni, Tukesh; Das, A.S.; Dutt, J.K. (Journal of sound and vibration, 2020)
Rotor-shaft-bearing system is an integral part of the engine and propulsion system of a ship. Ships are subject to water-waves which cause large rigid body motion of the ship hull involving all six degrees of freedom. This large time-varying ship-motion causes parametric excitation to the flexible rotor mounted on the ship, and may generate high vibratory response of the rotor, although fairly balanced. This paper proposes active control of lateral vibration in such rotors with a suitably placed electromagnetic actuator and compares simulated performance (response amplitude and control current) of different control laws, namely, (i) PD, (ii) PID and (iii) two novel control laws inspired by the mechanical models of a viscoelastic semi-solid. Realistic ship motion during sea-keeping conditions is generated by numerically solving the governing differential equations of motion of a ship under the action of water waves, using indigenously developed code. The equations of motion of the discretized rotor continuum subject to forces from conventional bearings, base motion and the actuator are obtained with respect to a non-inertial reference frame attached to the moving rotor base. Multi-objective optimization of control gains is carried out to obtain minimum rotor-disk response at the expense of the optimum control current. Numerical simulations reveal that the novel control law proposed in (iii) is the most efficient in terms of vibration response and control cost.